Cultivo da soja em áreas de entorno do Mosaico das Unidades de Conservação do Jalapão, na região do Matopiba - Gamba, Fábio Brega; Collicchio, Erich (Revista Liberato, 2018)
Oleaginous originated from countries with a predominance of temperate climate, soybean adapted to the tropical climate of Brazil and its culture was better established here. The increase in its production was due to the growing demand for protein foods by the developed countries, since it has been possible to produce more protein per ha than any other type of crop with the soybean crop. The objective of the present work was to analyze the expansion of the soybean crop in the Cerrado, with emphais on the municipalities located around the Mosaic of Jalapão Conservation Units in the Matopiba region, through the use of official data. It was verified that the conservation units are shown as good strategic instruments of protection of the native vegetation and of animal species in the Cerrado. The Mosaic of Jalapão Conservation Units is an example of areas created for this purpose, but is increasingly under pressure from the agribusiness developed in the productive districts inserted or bordering this set of conservation units.